2017
DOI: 10.1007/s12041-017-0758-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of argonaute, Dicer-like, and RNA-dependent RNA polymerase genes in cucumber (Cucumis sativus L.) in response to abiotic stress

Abstract: Posttranscriptional control of gene expression can be achieved through RNA interference when the activities of Dicer-like (DCL), argonaute (AGO) and RNA-dependent RNA polymerase (RDR) proteins are significant. In this study, we analysed the expression of seven AGO, five DCL and eight RDR genes in cucumber under cold, heat, hormone, salinity and dehydration treatments using quantitative reverse-transcription PCR (qRT-PCR). All CsAGO, CsDCL and CsRDR genes were differentially expressed under abiotic stress treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Global climate change threatens crop yield by imposing ambient pressures such as cold, drought, salinity, heat and other abiotic and biotic stresses [1]. Numerous studies indicate that small RNAs (sRNAs) have important roles in gene expression regulation during the abiotic and biotic stresses in all plants [26].…”
Section: Introductionmentioning
confidence: 99%
“…Global climate change threatens crop yield by imposing ambient pressures such as cold, drought, salinity, heat and other abiotic and biotic stresses [1]. Numerous studies indicate that small RNAs (sRNAs) have important roles in gene expression regulation during the abiotic and biotic stresses in all plants [26].…”
Section: Introductionmentioning
confidence: 99%
“…The TFs MYB, Dof, ERF, NAC, MIKC_MADS, WRKY and bZIP families might play significant role in regulating RNAi genes. Particularly those of ERF, NAC, WRKY and bZIP families, which are the top four families those contained 29,20,20 and 10 TFs and accounted 57.66% of the total identified TFs ( Supplementary Table S3). This finding indicated that those TFs could be important in regulating RNAi genes.…”
Section: Regulatory Relationship Between Tfs and Rnai Genesmentioning
confidence: 99%
“…The EST mining results from the PlantGDB database indicated that the RNAi genes of C. sinensis expressed in multiple important tissue and organs. However, the expression evidence of the RNAi genes in several species has been reported which showed that the RNAi genes have expression in leaf, root, flower, seeds and in others tissue [13,[23][24][25][26][27][28][29][30]73].…”
Section: In Silico Expressed Sequence Tag (Est) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Argonaute (Ago) proteins can mediate target silencing by translational repression and de-adenylation coupled with mRNA decay, which has an impact on diverse biological processes ( Sasaki and Tomari, 2012 ). Many Agos that respond to chilling stress (CS) are found in various plant species, such rice ( Kapoor et al, 2008 ), wheat ( Meng et al, 2013 ), and cucumber ( Gan et al, 2017 ). The identification of VvAgo1 in response to CS ( Bao et al, 2013 ) suggests that fungal Agos are responsible for chilling stress-response similar to plant Agos.…”
Section: Introductionmentioning
confidence: 99%